ANALISIS YURIDIS STRATEGI PENGEMBANGAN USAHA MIKRO KECIL MENENGAH PADA MASA PANDEMI COVID-19 UNTUK MEWUJUDKAN KETAHANAN EKONOMI KERAKYATAN (STUDI PENELITIAN DI DINAS KOPERASI DAN USAHA MIKRO KOTA BATAM) - Ranti Rivadianti; Siti Nurkhotijah; Christiani Prasetya Sari (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
In the juridical analysis of the strategy for developing micro, small and medium enterprises during the COVID-19 pandemic, it aims to discuss legal arrangements regarding the development strategy of MSMEs during the Covid-19 pandemic and the factors that become obstacles in developing MSMEs during the pandemic as well as solutions from the government for the development of MSMEs. during the covid-19 pandemic. MSMEs are people's businesses that currently receive attention and privileges mandated by law, including business credit assistance with low interest, ease of business license requirements, business development assistance from government agencies, and several other facilities. The method used in this research is empirical normative. In obtaining secondary data, researchers used a normative approach and in obtaining primary data, researchers used empirical research methods through field research. Sources of data in this study using literature, field and interview methods, as well as secondary data and primary data. Researchers also use data analysis in the form of qualitative analysis. The results showed that Batam Mayor Regulation Number 49 of 2020 concerning the Implementation of Discipline and Law Enforcement of Health Protocols as an Effort for Prevention and Control of Corona Virus Disease 2019 in Batam City. This Batam Mayor Regulation is a guideline for implementing discipline and law enforcement in the prevention and control of Covid-19 in Batam City. The Batam city government has been right in implementing restrictions on operating hours for MSMEs and public places and the micro-enterprise cooperative service has also helped develop MSMEs by conducting socialization. The Batam city government is expected to consistently provide counseling and socialization to MSMEs.Keywords: Development Strategy, MSMEs, Covid-19 Pandemic